Evaluation of Sexual Dysfunction in Female Patients with Fibromyalgia Syndrome : Sexual Dysfunction in Female Patients with Fibromyalgia Syndrome - Barut, Ayşe Berhoğlu; Barut, Osman (International Journal of Medical Science and Clinical Research Studies, 2021)
Objectives: The aim of our study is to determine the presence and quality of sexual function in women with fibromyalgia syndrome and to compare it with the normal population. Materials and methods: In our case-control study was conducted on sexually active 46 fibromyalgia patients who were diagnosed according to the American College of Rheumatology (ACR) criteria and 35 healthy control aged between 20-55. The data was collected with Beck Depression Inventory (BDI), Female Sexual Function Index (FSFI), Fibromyalgia Impact Questionnaire (FIQ) and Visual Analogue Scale (VAS). The clinical characteristics of both groups were compared and the relationships between FSFI and clinical parameters were evaluated. Results: Both groups were similar in terms of age, duration of marriage, number of children, family type and educational level. The mean duration of complaints in women with fibromyalgia was 5.62 (3.45) years, FIQ score was 59.8 (12.2) and VAS score was 7 (2). FSFI score was 13.2 (8.1) in group 1 and 32.1 (5.2) in group 2 (P<0.05). The mean scores of FIQ, BDI and VAS in group 1 were signiﬁcantly higher than those in group 2 (P<0.05). In addition, a significant negative correlation was determined between the total FSFI score and FIQ and BDI scores in group 1. Conclusion: Negative effects of sexual dysfunction on female patients should be considered when evaluating fibromyalgia. It should be noted that sexual functon assessment must be a part of fibromyalgia syndrome treatment. Further studies are needed to elucidate the relationship between fibromyalgia and sexual dysfunction